2016
DOI: 10.4172/2161-105x.1000376
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics Modeling of Extrathoracic Airway Flush: Evaluation of High Flow Nasal Cannula Design Elements

Abstract: Objective: High flow nasal cannula (HFNC) is an evolving respiratory therapy whereby high flow rates of conditioned breathing gas are delivered into the nasal cavity to purge anatomical dead space of CO 2 rich expired gas. The aim of this project was to create a computational fluid dynamics (CFD) model to evaluate the fluid patterns in the human nasal and pharyngeal cavities with HFNC application, and quantify time to purge for two cannula configurations.Methods: Three-dimensional geometry of the human airway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Optiflow cannulae have independent flow channels to each prong and wider bore tubing, whereas the Precision Flow cannulae have a common flow channel and narrower tubing. Three-dimensional computational fluid dynamic models have shown that smaller bore cannulae may produce a higher flow velocity, 37 and we speculate that a similar phenomenon occurs with the Precision Flow cannulae. Improved CO 2 clearance with HFNC helps explain reported clinical reductions in breathing frequency, arterial CO 2 , and work of breathing in patients treated with HFNC.…”
Section: Discussionsupporting
confidence: 55%
“…Optiflow cannulae have independent flow channels to each prong and wider bore tubing, whereas the Precision Flow cannulae have a common flow channel and narrower tubing. Three-dimensional computational fluid dynamic models have shown that smaller bore cannulae may produce a higher flow velocity, 37 and we speculate that a similar phenomenon occurs with the Precision Flow cannulae. Improved CO 2 clearance with HFNC helps explain reported clinical reductions in breathing frequency, arterial CO 2 , and work of breathing in patients treated with HFNC.…”
Section: Discussionsupporting
confidence: 55%
“…HVNI administration employs a small-bore nasal cannula prong, imparting greater velocity to the gas flow. This has been demonstrated to provide a mechanistic advantage to flush the accessible deadspace in the upper airway, likely through creation of increased turbulent kinetic energy ( 37 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…A high-flow nasal cannula (HFNC) is widely used in preterm infants to provide tolerable and comfortable respiratory support. 1 The benefits of an HFNC include a secure oxygen supply, 2 heat humidification of the airway, 3,4 CO 2 washout in the anatomical dead space, 5,6 and mild positive pressure. 6,7 Studies have reported significant correlations between flow rate and airway pressure generated by an HFNC in preterm infants.…”
mentioning
confidence: 99%